( | 236 | + | 5 | X | ) | ÷ | ( | 51 | + | X | ) | = | 47 10 |
Multiply both sides of the equation by: | ( | 51 | + | X | ) |
( | 236 | + | 5 | X | ) | = | 47 10 | ( | 51 | + | X | ) |
236 | + | 5 | X | = | 47 10 | ( | 51 | + | X | ) |
236 | + | 5 | X | = | 47 10 | × | 51 | + | 47 10 | X |
236 | + | 5 | X | = | 2397 10 | + | 47 10 | X |
5 | X | − | 47 10 | X | = | 2397 10 | − | 236 |
3 10 | X | = | 2397 10 | − | 236 |
3 10 | X | = | 37 10 |
X | = | 37 10 | ÷ | 3 10 |
= | 37 10 | × | 10 3 |
= | 37 | × | 1 3 |
X | = | 37 3 |
X | = | 12.333333 |